Peran Sektor Informal dalam Penyerapan Tenaga Kerja di Kecamatan Labang Kabupaten Bangkalan - Nora Kamelia; Jaka nugraha (Jurnal Ekonomika : INDEPENDEN, 2021)
The informal sector is a small scale business unit whose business activities are outside gorvernment regulations. Labor absorption is a situation where the workforce is already accommodated in a company. While economic growth is the driving force for economic activity in an area to encourage the growth of goods and services production so as to provide jo opportunities.This study aims to determine the role o f the informal sector in employment in Labang District, Bangkalan Regency. The method used inthis research in descriptive qualitative method with data collection through interview techniques. Based on the research results, it can be concluded that the informal sector plays a major role in the absorption of labor for people in Labang District by creating their own employment opportunities for themselves or their families. According to the results of field research, informal sector activities in the Suramadu area cannot be separated from the economic background of the familiy. Where the informal sector provides possibilities for workers who do not have the opportunity to work in the informal sector. The majority of informal sector workers in the Suramadu area have low education so that their skills and abilities are very limited. People in Labang District prefer to open stall by taking advantage of the Suramadu bgridge infrastructure development so that they can attract consumers to road users. This is because it is easy to run a business in the informal sector so that it can open their own jobs that are owned by individuals or families. Keywords: The Informal Sector, employment,economic growth